THE CALCULATION METHOD FOR SPHERICAL OPERATORS - Constantin Cristinel GIRDU (Fiabilitate şi Durabilitate)
The model was introduced by Malkin (ECM) to describe the behavior of rare earth metals (RE) andtransition metals (TM) used as an impurity ion crystal field of ligands belonging to the crystal (host matrix).Thecalculation is quite easy for those who apply irreducible tensor operators MAPLE programming introduced byMalkin.